The Influence of Entrepreneurial Motivation and Family Environment on Entrepreneurial Interest: The Mediating Role of Self-Efficacy - Patriandi Nuswantoro; Hajar Dewantara; Muhammad Aras (Pinisi Journal of Entrepreneurship Review, 2025)
University students play a crucial role in fostering job creation through entrepreneurship. This study investigates the effect of entrepreneurial motivation and family environment on entrepreneurial interest, with self-efficacy as a mediating variable. A quantitative approach with an explanatory descriptive design was employed. The study involved 102 undergraduate students selected through proportional random sampling. Data were gathered using an online questionnaire and analyzed using SPSS version 27. The results indicate that entrepreneurial motivation does not have a direct significant effect on entrepreneurial interest but has a positive and significant effect on self-efficacy. The family environment positively and significantly influences both self-efficacy and entrepreneurial interest. Additionally, self-efficacy has a positive and significant effect on entrepreneurial interest. Furthermore, entrepreneurial motivation significantly affects entrepreneurial interest indirectly through self-efficacy. Similarly, the family environment has a significant indirect effect on entrepreneurial interest through self-efficacy. These findings underscore the importance of fostering self-efficacy among students to strengthen their entrepreneurial interests. Moreover, the family environment plays a critical role in shaping both the self-confidence and entrepreneurial drive of future entrepreneurs. The study contributes to the broader understanding of psychological and social factors influencing entrepreneurial behavior in higher education contexts.